2017
DOI: 10.1002/zaac.201700328
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Photoinitiated Synthesis and Phase‐Transfer Separation of Bismuth Nanoparticles

Abstract: Abstract. Bismuth nanoparticles were obtained via sequential photoinitiated synthesis and phase-transfer separation. Specifically, BiBr 3 was used as a starting material in propylene carbonate (PC) as the polar phase, which was topped by heptane (Hep) as the non-polar phase containing oleylamine (OA) as the phase-transfer agent. In a photoreactor set-up, this two-phase system was thoroughly mixed and illuminated by broad-band UV light emitted by a high-pressure Xe lamp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Similarly, Brütsch et al , observed a deep black colour when they synthesized Bi nanoparticles into organic solvent by photo-reduction of BiBr 3 . 33 HR-TEM analysis was performed to confirm this. Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Brütsch et al , observed a deep black colour when they synthesized Bi nanoparticles into organic solvent by photo-reduction of BiBr 3 . 33 HR-TEM analysis was performed to confirm this. Fig.…”
Section: Resultsmentioning
confidence: 90%
“…This distance can be attributed neither to Bi nor to Bi 2 O 3 . 33 This distance could be compatible with the interreticular distances of the (111) planes of the fluorinated phases, BiO 0.5 F 2 (JCPDS 24-0147), the phase observed in case of thin films deposition, but is also compatible with Bi 7 O 5 F 11 (JCPDS 50-0003) or BiF 3 (in cubic (JCPDS 51-0944) or orthorhombic (JCPDS 70-2407) phases) without being able to specifically distinguish them. On the other hand, the BiOF (JCPDS 73-1595) phase does not seem to be obtained, the position of its most intense peak corresponding to smaller interreticular distances.…”
Section: Resultsmentioning
confidence: 99%
“…Though the precise composition of the proposed iodobismuthate solution precursor was not identified, the characteristic orange color of the solution observed during the second stage of the reaction is likely due to a ligand-to-metal charge transfer (LMCT) transition between iodide ligands and coordinated Bi 3+ cation(s) [29,[32][33][34][35][36]. The observation that our standard reaction conditions result in elemental bismuth when using BiI 3 , BiOI, or BiBr 3 as starting materials, but not when using BiCl 3 , indicate that the LMCT is responsible for initiating Bi 0 formation at a reaction temperature of 180 °C.…”
Section: Investigation Of the Mechanism Of Bi Np Formationmentioning
confidence: 99%